THE FUTURE OF METALLURGY: INTELLIGENT TECHNOLOGIES, DIGITAL TWINS, AND SUSTAINABLE DEVELOPMENT - Asimova Feruza Abdusattorovna; Zagidullina Kamila Rafailovna; Sayfutdinova Nigina Furkatovna (Ecominds Press, 2025)
Modern metallurgy increasingly relies on innovative approaches such as digital twins, intelligent technologies, and automation to enhance production efficiency. This article explores the significance of new technologies in ensuring energy efficiency, optimal resource utilization, and sustainable development. Additionally, it discusses the potential for process optimization through the implementation of digital twin models and the opportunities for a technological revolution in the metallurgical industry.
Keywords: Metallurgy, intelligent technologies, digital twins, sustainable development, energy efficiency, automation, innovations.